Food transgressions making sense of contemporary food politics - Goodman, Michael K. 1969-; Sage, Colin (Farnham, Surrey, England Ashgate Publishing Limited, 2014)
Reconnecting so-called alternative food geographies back to the mainstream food system - especially in light of the discursive and material 'transgressions' currently happening between alternative and conventional food networks, this volume critically interrogates and evaluates what stands for 'food politics' in these spaces of transgression now and in the near future and addresses questions such as: What constitutes 'alternative' food politics specifically and food politics more generally when organic and other 'quality' foods have become mainstreamed? What has been the contribution so far of an 'alternative food movement' and its potential to leverage further progressive change and/or make further inroads into conventional systems? What are the empirical and theoretical bases for understanding the established and growing 'transgressions' between conventional and alternative food networks? Offering a better understanding of the evolving position of the corporate food system vis a vis alternative food networks, this book considers the prospects for economic, social, cultural and material transformations led by an increasingly powerful and legitimated alternative food network.
Food transgressions : ethics, governance and geographies / Michael K. Goodman and Colin Sage -- Pathways of transformation or transgression? Power relations, ethical space, and labour rights in Kenyan agri-food value chains / Valerie Nelson, Anne Tallontire, Maggie Opondo, and Adrienne Martin -- Of red herrings and immutabilities : rethinking fairtrade's ethic of relationality among cocoa producers / Amanda Berlan and Catherine Dolan -- Greater than the sum of the parts? Unpacking ethics of care within a community supported agriculture scheme / Rosie Cox, Moya Kneafsey, Lewis Holloway, Elizabeth Dowler, and Laura Venn -- Polite transgressions? Pleasure as economic device and ethical stance in slow food / Federica Davolio and Roberta Sassatelli -- Eating powerful transgressions : (Re)Assessing the spaces and ethics of organic food in the UK / Michael K. Goodman -- Transgressing retail : supermarkets, liminoid power, and the metabolic rift / Jane Dixon, Libby Hattersley, and Bronwyn Isaacs -- Making meat collectivities : entanglements of geneticisation, integration, and contestation in livestock breeding / Lewis Holloway, Carol Morris, David Gibbs, and Ben Gilna -- Making and un-making meat : cultural boundaries, environmental thresholds, and dietary transgressions / Colin Sage -- Knowing Brand Wales : agro-food transitions in firms, innovation, and governance / Carla De Laurentis and Philip Cooke -- Food for poorer people : conventional and 'alternative' transgressions? / Martin Caraher and Elizabeth Dowler.
Includes bibliographical references and index.
Keywords: Food industry and trade -- Political aspects; Food industry and trade -- Moral and ethical aspects; Food supply -- Moral and ethical aspects